Determination of some physical-chemical properties of biofortification soft wheat and flour of the varieties “Treska” - Menkinoska, Marija; Stanoev, Vinko; Pavlova, Valentina; Blazevska, Tatijana; Stamatovska, Victorija; Gjorgovska, Natasa (Journal of Engineering & Processing Management, 2017)
Cereal crops as a basic food for humans, little is used as a grain, but with milling they are processed in the milling products: flour, meal, flakes and bran. Determining the content of some ingredients, such as protein, ash, wet gluten, fat, etc. in food products is important because they are present in the raw materials and final products. The importance of knowing the physical and chemical properties of wheat and flour is due to the determination of quality and kind of flour which is produced after milling process. The aim of this research is to examine the influence of Fe-EDTA fertilizers through soil, foliar and soil +foliar application on some physical and chemical properties of bio-fortification soft wheat and flour of the varieties , Treska , During the investigation we determined the highest ash content in the seed obtained with soil + foliar application of iron, while in the flour was measured the highest ash content by soil application of iron. We concluded that the supplement iron in soil increase the percentage of protein in the grain and flour. We found that soil + foliar application of iron leads to a significant increase of % fat and wet gluten in grain and flour compared to soil or foliar application of chelating fertilizers. It might be concluded that the agronomic bio-fortification with Fe-EDTA soil + foliar application and Fe-EDTA soil leads to improved examined physical - chemical properties of wheat and flour.